Cost-benefit analysis of BRAC's sericulture programme - Halder, Shantana R. (BRAC, 2019)
The Sericulture Programme of BRAC is one of the most ambitious among BRAC sector programmes. Since 1992 BRAe has gone through a large scale expansion of the plantation programme. Major components of the programme are: a) nursery, b) mulberry plantation, c) rearing of the silkworms, d) reeling, and e) weaving. The main objective of the study was to measure the efficiency of the programme by doing a cost benefit analysis from the participants' as well as the organizers' point of view. The specific objectives of the study were: 1) to determine employment created by BRAC to measure the opportunity cost of time and BRAC's achievements in this area; 2) to determine the programme costs and returns for calculating the profitability of the different components of the programme; 3) to calculate accounting and economic profit to determine the viability of programme participants; and 4) to identify the socia-economic constraints on programme sustainability. The study considered four different stages of measuring programme viability. In the first stage the employment generation in each component of the programme was detennined to calculate the minimum opportunity cost of time and BRAC's achievements. In the second stage both programme input and output records were used to calculate the total cost of the programme and the revenue it earned. Major components of fixed and variable costs may differ in different programme activities which were also considered. In the third stage participants viability was investigated. Indicators used to measure participants viability were: 1) profit per unit of input; 2) average rate of return on investment =profit/total investment on fixed assets; 3) average rate of return on operating cost =profit/operating cost; 4) yield or value of output per unit of major input; and 5) amount or cost of input per unit of output. The programme is treated as economically viable when the actual rate of return exceeds the market rate of interest. The fourth stage described the programme viability. Monthly receipts and expenditure statements of sericulture programme were used to evaluate it. The study tried to focus on how to increase the physical output to its maximum level and to reduce costs to its minimum. Primary data were collected from a random sample of 492 programme participants from 10 AOs including 26 sapling growers and 300 silk worm rearers. Due to the fact that reeling, pedal spinning and weaving were not done in every selected AOs, fifty seven workers from three reeling centres, 64 pedal spinners from five AOs and 45 weavers from three BRAe weaving programme areas were selected.